2021
DOI: 10.3390/ma14081988
|View full text |Cite
|
Sign up to set email alerts
|

Overview of HSS Steel Grades Development and Study of Reheating Condition Effects on Austenite Grain Size Changes

Abstract: This review paper concerns the development of the chemical compositions and controlled processes of rolling and cooling steels to increase their mechanical properties and reduce weight and production costs. The paper analyzes the basic differences among high-strength steel (HSS), advanced high-strength steel (AHSS) and ultra-high-strength steel (UHSS) depending on differences in their final microstructural components, chemical composition, alloying elements and strengthening contributions to determine strength… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 78 publications
0
39
0
Order By: Relevance
“…Microalloying is an effective way in managing the processing of advanced high strength steels by their influence on recrystallization and transformation and in controlling the properties by microstructural refinement and precipitation hardening [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Microalloying is an effective way in managing the processing of advanced high strength steels by their influence on recrystallization and transformation and in controlling the properties by microstructural refinement and precipitation hardening [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…However, high-strength steels have lower formability and greater springback in comparison with conventional steels used for drawing, the main reason for that is the higher value of the yield strength and lower ductility of these steels (Fig. 1) [1,2]. The TRIP steels, or Transformed Induced Plasticity steels, have higher values of mechanical properties (yield strength and tensile strength) if compared with conventional steels [3].…”
Section: Introductionmentioning
confidence: 99%
“…The microstructure evolution of high-strength steels during hot and cold rolling and cooling from an austenitizing temperature were investigated [11,12]. Zhao et al [13] reported that the refinement and strengthening of advanced high-strength steels were achieved by thermomechanical processing.…”
Section: Introductionmentioning
confidence: 99%